PELAKSANAAN KEGIATAN EKSTRAKURIKULER SENI TARI DI SMP NEGERI 5 PADANG - Ziqra Aulia Rahmi; Fitri, Hasminda (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to describe the implementation of dance extracurricular activities at SMP Negeri 5 Padang. The research uses a qualitative approach with a descriptive method. The research subjects are students who participate in dance extracurricular activities with Mandeh creative dance material. Data collection techniques include observation, interviews, literature study, and documentation, while data analysis is carried out through reduction, presentation, and drawing conclusions. The research results show that the implementation of the activities includes planning, execution, and evaluation stages. The activities were conducted through lectures and demonstrations to enhance students' mastery of movements, teamwork, and expression. The challenges faced included limited practice space, inconsistent attendance, and low interest among male students. However, the space limitation was addressed by using the school field as an alternative practice area. Overall, these activities had a positive impact on the students' creativity, skills, and self-confidence.